Involvement of Inflammation in Venous Thromboembolic Disease: An Update in the Age of COVID-19 - Poredos, Peter; Poredos, Pavel (Seminars in Thrombosis and Hemostasis, 2021)
The inflammatory process is strongly involved in the pathophysiology of venous thromboembolism (VTE) and has a significant role in disease prediction. Inflammation most probably represents a common denominator through which classical and nonclassical risk factors stimulate thrombotic process. Inflammation of the venous wall promotes the release of tissue factor, inhibits the release of anticoagulant factors, and hampers endogenous fibrinolysis. Systemic inflammatory response also inhibits restoration of blood flow in the occluded vessel. Recent studies indicate that increased inflammatory response (“cytokine storm”) is related to prothrombotic state and thromboembolic events in patients with coronavirus disease 2019 (COVID-19). The growing evidence of involvement of inflammation in the pathogenesis of VTE indicates the importance of anti-inflammatory treatment and prevention of VTE. While aspirin was shown to be effective in prevention of recurrent venous thrombosis after treatment with anticoagulant drugs, some other anti-inflammatory drugs like nonsteroidal anti-inflammatory agents may have prothrombotic effect, thus potentially increasing the risk of VTE. Recently, new specific anti-inflammatory drug inhibitors of inflammatory markers that have been shown to be involved in the pathogenesis of VTE are being searched. As thrombogenesis is based on activation of coagulation provoked by inflammation, then prevention and treatment of VTE should include both anticoagulant and anti-inflammatory agents. Combined treatment is related to increased risk of bleeding complications, therefore subtherapeutic doses of both drugs should be used to improve the efficacy of management of VTE without increasing the risk of bleeding.
Keywords: inflammation; venous thromboembolism; risk factors; COVID-19; anti-inflammatory treatment